Endometriotic lesions exhibit distinct metabolic signature compared to paired eutopic endometrium at the single-cell level - Meruert Sarsenova; Ankita Lawarde; Amruta D. S. Pathare; Merli Saare; Vijayachitra Modhukur; Pille Soplepmann; Anton Terasmaa; Tuuli Käämbre; Kristina Gemzell-Danielsson; Parameswaran Grace Luther Lalitkumar; Andres Salumets; Maire Peters (Communications Biology, 2024)
Abstract Current therapeutics of endometriosis focus on hormonal disruption of endometriotic lesions (ectopic endometrium, EcE). Recent findings show higher glycolysis utilization in EcE, suggesting non-hormonal strategy for disease treatment that addresses cellular metabolism. Identifying metabolically altered cell types in EcE is important for targeted metabolic drug therapy without affecting eutopic endometrium (EuE). Here, using single-cell RNA-sequencing, we examine twelve metabolic pathways in paired samples of EuE and EcE from women with confirmed endometriosis. We detect nine major cell types in both EuE and EcE. Metabolic pathways are most differentially regulated in perivascular, stromal, and endothelial cells, with the highest changes in AMPK signaling, HIF-1 signaling, glutathione metabolism, oxidative phosphorylation, and glycolysis. We identify transcriptomic co-activation of glycolytic and oxidative metabolism in perivascular and stromal cells of EcE, indicating a critical role of metabolic reprogramming in maintaining endometriotic lesion growth. Perivascular cells, involved in endometrial stroma repair and angiogenesis, may be potential targets for non-hormonal treatment of endometriosis.